2014
DOI: 10.1002/chem.201405580
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Lipidic Cubic Phase: Triggered Release and Sequestration of Guest Molecules

Abstract: New stimuli-responsive nanomaterials, made up of host-guest lipidic cubic phases (LCPs) are presented. These biocompatible, stable, transparent and water-insoluble LCPs are composed of monoolein (MO) as a neutral host, and small amounts of one of three judiciously designed and synthesized designer lipids as guest that preserve the structure and stability of LCPs, but render them specific functionalities. Efficient pH- and light-induced binding, release and sequestration of hydrophilic dyes are demonstrated. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…1 These results are in good agreement with our previously published work. 7 Negrini et al have demonstrated that drug release from a Pn3m cubic phase is ca. 4 times faster than that from a hexagonal phase (H II ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 These results are in good agreement with our previously published work. 7 Negrini et al have demonstrated that drug release from a Pn3m cubic phase is ca. 4 times faster than that from a hexagonal phase (H II ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Experiments with MG in LCPs composed of MO/1/PBS = 59:1:40 (%, w/w) demonstrate a fast release of the hydrophilic dye in the absence of electrostatic interactions between the lipid head groups and the dye embedded in the aqueous channels, with 45% of the dye released within 8 h. These results are in perfect agreement with the control of release via host−guest electrostatic interactions in cubic phases reported recently. 7,34 Upon the addition of the anionic lipid OA at levels of 1 and 5% (w/w) into the LCPs at pH 7.4, the negatively charged carboxylate headgroup binds the dye more efficiently than the neutral glycerol headgroup of MO ( Figure 2). Increasing the amount of OA from 1 to 5% does not alter the release profile, because already at a level of 1%, the binder (OA) is in large excess with respect to the positively charged dye (n OA /n MG = 364:1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these investigations are beneficial for the potential use of these nano-objects in a range of biotechnological applications, where the stability of the original phase and inter-transitions could play important roles, e.g. for drug delivery applications [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%